Therapeutic Dose Response of Acoustic Cluster Therapy in Combination With Irinotecan for the Treatment of Human Colon Cancer in Mice - Bush, Nigel; Healey, Andrew; Shah, Anant; Box, Gary; Kirkin, Vladimir; Kotopoulis, Spiros; Kvåle, Svein; Sontum, Per Christian; Bamber, Jeffrey (Frontiers in Pharmacology, 2019)
Acoustic Cluster Therapy (ACT) comprises co-administration of a formulation containing microbubble-microdroplet clusters (PS101) together with a regular medicinal drug and local ultrasound (US) insonation of the targeted pathological tissue. PS101 is confined to the vascular compartment and when the clusters are exposed to regular diagnostic imaging US fields, the microdroplets undergo a phase-shift to produce bubbles with a median diameter of 22 µm. Low frequency (500 kHz), low mechanical index (MI=0.20) ultrasound is then applied to drive oscillations of the deposited ACT bubbles to induce a range of biomechanical effects that locally enhance extravasation, distribution and uptake of the co-administered drug, significantly increasing its therapeutic efficacy. The therapeutic efficacy of ACT with irinotecan (60 mg/kg i.p.) was investigated using three treatment sessions given on day 0, 7 and 14, on subcutaneous human colorectal adenocarcinoma xenografts in mice. Treatment was performed with three back-to-back PS101+US administrations per session with PS101 doses ranging from 0.40 to 2.00 mL PS101/kg body weight (n=8 to 15). To induce the phase shift, 45 s of ultrasound at 8 MHz at an MI of 0.30 was applied using a diagnostic ultrasound system; low frequency exposure consisted of 1 or 5 min at 500 kHz with an MI of 0.20. ACT with irinotecan induced a strong, dose dependent increase in the therapeutic effect (R2=0.95). When compared to irinotecan alone, at the highest dose investigated, combination treatment induced a reduction in average normalised tumour volume from 14.6 (irinotecan), to 5.4 (ACT with irinotecan, p=0.002) on day 27. Median survival increased from 34 days (irinotecan) to 54 (ACT with irinotecan, p=0.002). Additionally, ACT with irinotecan induced an increase in the fraction of complete responders; from 7% to 26%. There was no significant difference in the therapeutic efficacy whether the low frequency ultrasound lasted 1 or 5 minutes. Furthermore, there was no significant difference between the enhancement observed in the efficacy of ACT with irinotecan when PS101+US was administered before or after irinotecan. Results for both mean tumour volume (on day 27) and median survival indicate that the PS101 dose response was linear in the range investigated.